New cognitive radio channel model and the analysis of its capacity - XIE Xian-zhong; YANG Zhi-hua; ZHENG Yi (Tongxin xuebao)
New cognitive radio channel model is the combination of the interweave channel and the interference channel.By introducing the switch concept,the spectrum hole sensing was combined the channel model.So a new cognitive radio two-user channel model with partial knowledge of the primary messages at the cognitive transmitter was proposed.First,the channel between the primary user and the second user was modeled as a compression channel and introduced the compression rate.Then,the channel capacity was analyzed and calculated.Finally,numerical results illustrate the validity of the new channel model and the advantage of its capacity.